A Phenomenological Study on Teachers’ Beliefs on Teaching Evaluation Practice for Space Design Studies in Higher Education Institutions at Xi’an China - Lai Fan; Wong Teck Foo (International Journal of Social Sciences: Current and Future Research Trends, 2023)
This study employs a qualitative phenomenological emic research approach to explore the teaching beliefs and evaluation practices of instructors in space design courses (SDCs) within higher education institutions (HEIs) in Xi’an, China. In the context of globalization, professionalization, and large-scale transnational education, it investigates how instructors perceive and implement teaching assessments and what beliefs and values are reflected in their teaching practices. Through in-depth interviews with 17 spatial design course instructors, this research reveals four major themes: Teaching Assessment and Improvement, Instructors’ Teaching Beliefs, Validity and Methods of Teaching Assessment, and Teaching Resources and Assessment Materials. Findings indicate that instructors generally consider teaching assessment to play a crucial role in enhancing teaching quality but hold varying perspectives on its validity and long-term impact. Additionally, instructors’ teaching beliefs are diverse and heavily influenced by their personal philosophies, experiences, and professional backgrounds. These beliefs manifest and are applied in various ways in teaching practices, providing theoretical support and guidance for instructors’ teaching decisions. The findings of this study offer a fresh perspective for understanding and improving the teaching of spatial design courses, providing insights for further theoretical research and teaching practices.